Analisis Penerapan Green Supply Chain Management (GSCM) pada Coffee Shop X menggunakan Pendekatan Green SCOR - Natalia Dassi Melolo; Vivi Defitri Septresia; Juan Fernandes Hutabarat; Aurel Hangga Ginanta K.; Ade Rahmat Hidayatullah (Jurnal Logic: Logistics & Supply Chain Center, 2026)
This study aims to analyze the implementation of Green Supply Chain Management (GSCM) at Coffee Shop X using the Green Supply Chain Operations Reference (Green SCOR) approach supported by Likert-scale Key Performance Indicator (KPI) measurements. The study used a quantitative descriptive method enriched with qualitative data through observation, interviews, literature studies, and questionnaires distributed to seven respondents involved in supply chain activities. A total of 23 KPI indicators were compiled based on the five Green SCOR processes, namely Plan, Source, Make, Deliver, and Return. The results showed that the implementation of GSCM at Coffee Shop X obtained an overall average score of 4.29, which is included in the very good category. The Make process was the aspect with the highest performance due to the implementation of consistent production standards and the reuse of coffee grounds as fertilizer. Meanwhile, the Return process received the lowest score and still requires improvement, especially in a more structured waste management system. Several recommendations resulted include optimizing inventory control, determining safety stock, reducing the use of single-use plastics, and strengthening the waste management system to support more sustainable operations.